Synthesis and characterisation of nitrogen and magnesium-doped with titanium dioxide using sol-gel method - Razali, Nur’ Aliaa (2018)
Nowadays, too much pollution is happening surrounding us and one of them is water pollution which each becoming more severe and worse every day. One of the sources of water pollution comes from the industry which used dyes either excessively or not. In this particular case, the wastewater needs to be treated before releasing into the river or environment. Titanium dioxide (TiO2) is one of the most powerful semi-conductors that chemically stable and widely used in the photodegradation of wastewater process. However, TiO2 has wide band gap (3.2 eV) which only can be activated by using UV light. In order to overcome the weakness of this photocatalyst, doping technique is applied to modify the TiO2. By doping technique, the band gap can be reduced and the modified TiO2 can be applied under the visible light. The objectives of this research are to synthesise and analyse the characteristics of photocatalysts N-TiO2 and Mg-TiO2 on the phase and the morphology. Then, the objective is also to determine the maximum decolourisation efficiency on photodegradation Reactive Black 5 (RB 5) by N-TiO2 and Mg-TiO2 under visible light. In this research project, nitrogen and magnesium were used as dopants and sol-gel method is applied. Calcination temperatures were varied at 300 oC, 500 oC and 700 oC in order to analyse the phase and characteristics of samples at different calcination temperature. The results obtained from the experiment showed the band gap after doping for samples 0.5 wt.% Mg-TiO2 and N-TiO2 shifted to the lower value compared to the theory value of pure TiO2 (3.2 eV) which are between 2.75 eV-2.98 eV . The phase structure of N-TiO2 and Mg-TiO2 at 300 oC and 500 oC were observed as pure anatase and at 700 oC , a mixture of anatase and rutile were found. The decolourisation of RB 5 achieved the highest efficiency at 83.46 % for 0.9 wt.% N-TiO2 and 72.66 % for 0.7 wt.% Mg-TiO2. Kinetic studies of zero order, first order and pseudo-first order were tested and it was found that the reaction followed pseudo-first order.